Self-instruction manual "TCI" to improve the quality of monographic research work for second-year students at UNJBG Tacna-2012. - Apaza Chambilla, Nancy (2014)
Objetive: Propose and validate self-instructional manual "TCI" as a teaching strategy to improve the quality of the work of monographic research sophomores LELI of Vocational Academic Education School UNJBG of Tacna in the 2012 academic year. Method: The investigation is of applied type of quasi-experimental nature intervenes in the dependent variable: quality of works monographic research. For this purpose, the information obtained through the manual application auto instructive "TCI" which was applied to the experimental group, consisting of 30 students from the Professional Academic School of Education specializing in Language and Literature (LELI) was considered second academic year of Jorge Basadre Grohmann National University (UNJBG) of Tacna. Result: Self-instructional manual "TCI" is a teaching strategy to improve the quality of the work of monographic research students, as seen in the results of the experimental group (EG) of the present investigation; thereby also the validity of the manual shows. Conclusion: self-instructional manual "TCI" significantly affects the quality of work of monographic research sophomores Academic School of Vocational Education UNJBG LELI of Tacna in the 2012 academic year.